PENERAPAN KONSEP GEOGRAFI PADA BUKU TEKS GEOGRAFI KELAS XI SEMESTER GANJIL TERBITAN ERLANGGA TAHUN 2016 - bambang wiranto wiranto; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
Abstract This article created to analyze the application of the concept of geography in the class XI geography textbook published by Erlangga 2016 part of the odd semester.this research uses quantitative methods with a content analysis approach. The source of this research is a class XI geography textbook published by Erlangga 2016. The data analysis was performed using percentage technique. The results showed that the total number of paragraphs analyzed was 379,301 paragraphs contained geographic concept or 79% and 78 paragraphs did not contain geographic concept or 21%. Then on the questions in the textbook totaling 192, 113 questions contained the concept of geography or 59% and 79 of the questions did not contain the concept of geographyor 41%. Based on the results of the data analysis it can be concluded that the class XI geography textbook published by erlangga 2016 is part off the odd semester namely, the application of the concept geography is already high in the paragraph and questions, but from the questions containing the concept the majority is included in the LOTS (low order thingking skills) questions namely categories C1 and C2